Impactful educational transitions: Crossroads for physiotherapy education in South Africa? - Corlia Janse van Vuuren (AOSIS, 2022)
Background: Global changes in physiotherapy entry-level educational programmes to exit with a Doctorate or Master's degree have consequences if physiotherapy education, worldwide, is to remain professionally competitive. However, within the South African context, such global competitiveness should be carefully considered against the national healthcare needs and implementation of the National Health Insurance (NHI) programme, with a bigger emphasis on a skilled mid-level workforce, including physiotherapy technicians or community rehabilitation workers. Objectives: These competing interests are carefully considered, against the theoretical background of international DPT training; human resource and financial constraints in the South African healthcare sector; reforms of the South African health and educational sectors intended to address the inequalities of the past; the need for quality healthcare delivery and the professional reputation of physiotherapy in South Africa. Methods: A framework for physiotherapy education in South Africa, to move on from the current educational crossroads, is proposed through an integration of multiple theoretical perspectives. Results: The framework is based on the current challenges being experienced in physiotherapy education and healthcare service delivery, which could be addressed by changes in the education sphere. Conclusion: The baseline suggestions for (re)considering the current education environment for physiotherapy, as proposed in my article, are to ensure that the profession remains relevant and able to confront the current changes presented by the South African healthcare system, including the implementation of the NHI plan, whilst remaining globally aligned and competitive. Clinical implications: The suggested, reconsidered, educational framework for physiotherapy in South Africa could become pivotal in advancing the profession on both a national and international level, through further critical conversations.